EVALUASI PERHITUNGAN, PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN (PPh) PASAL 21 ATAS KARYAWAN TETAP (STUDI KASUS PADA KANTOR WILAYAH VI PT PEGADAIAN MAKASSAR) - Winarsih, Endang (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2022)
ABSTRACT This study aims to determine whether the Calculation, Withholding, Deposit, and Reporting of Article 21 Income Tax on Permanent Employees of Regional Office VI PT. Pegadaian Makassar has complied with the Director General of Taxes Regulation Number Per- 16/PJ/2016. This study uses a qualitative approach, the data sources used in this research are primary data in the form of data taken from the source and secondary data in the form of data obtained from reading, studying and understanding through other media sourced from literature, books, and documents and data collection techniques used are interviews and documentation. The results of this study indicate that the calculation, withholding, deposit and reporting of income tax (PPh) Article 21 is in accordance with the regulations of the Director General of Taxes Number Per-16/PJ/2016.